(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
The study investigated play facilities as predictor of pre-reading skills acquisition among preschoolers in Chanchaga Local Government Area of Niger State. Two research questions and two null hypotheses guided the study. The study adopted a correlation survey research design. The population of the study is 4087 preschoolers in the 29 early child care centers in all the public primary schools in Chanchaga Local Government Area of Niger state. A sample of 356 preschoolers were used for the study. Play Facilities Questionnaire (PFQ) and Pre-reading Skills Acquisition Rating Scale (PSARS) were used for data collection. The two sets of instrument were face-validated by three experts from Faculty of Education, University of Nigeria, Nsukka. Internal consistency reliability through Cronbach alpha gave a reliability coefficient for pre-reading rating scale as 0.886. The internal consistency reliability coefficients for the clusters of C and D are given as 0.81 and 0.74 respectively in pe-reading skills. Linear regression was used in answering the research question while t-test associated with linear regression was used in testing the formulated hypotheses at 0.05 level of significance. The finding showed that play facilities have a high predictive power on the acquisition of phonological awareness skills among preschoolers in Chanchaga Local Government Education Area. The finding showed that play facilities have a significant predictive power on the phonological awareness skills acquisition among preschoolers in Chanchaga Local Government Education Area. It was also shown that play facilities have a high predictive power on the acquisition of vocabulary skills among preschoolers in Chanchaga Local Government Education Area. Lastly it was found out that play facilities have a significant predictive power on vocabulary skills acquisition among preschoolers in Chanchaga Local Government Education Area. Based on the findings and conclusion, the following recommendations were made, that school authorities should provide audio-visual materials with phonological contents in order to help preschoolers acquire phonological awareness skills. Cartoons with word match and pronunciation content should be constantly used in the teaching of vocabularies in the preschools, for the acquisition of vocabulary skills.